Manipulating Public Perception: A Critical Discourse Analysis of Political Headlines on Pakistani Social Media - Shah, Muhammad Mubeen (Journal of Development and Social Sciences, 2025)
This study examines political headlines on Pakistani social media manipulate public perception. A critical discourse analysis (CDA) framework, combining Fairclough’s three-dimensional model with van Dijk’s socio-cognitive approach was used to analyze four randomly selected headlines from Facebook. The categories contain political, economic, and sports news where the research explores the strategic use of rhetorical devices, linguistic choices, and visual elements to disseminate power and ideology. Through textual, discursive practice, and socio-political practice analyses, the study reveals the prevalence of interrogative and exclamatory sentences, hyperbole, and selective information omission to create sensationalism and emotional engagement. The findings demonstrate how social media editors exploit these techniques to portray specific narratives, such as government weakness and opposition strength, and to politicize various news categories. The analysis further highlights the impact of visual cues, including images of prominent figures and strategic color schemes, in shaping audience interpretation. This research underscores the importance of critical media literacy in understanding the manipulative potential of social media headlines and emphasizes the need for ethical journalism practices, including transparency and fact-checking. It recommends future research to explore the long-term impact of these headlines on public opinion and the role of social media algorithms in news dissemination, while also advocating for stricter platform accountability and transparency in image manipulation.